Monetary functions of commercial banks - Brennan, Joseph (Statistical and Social Inquiry Society of Ireland, 1943)
The object of this paper is to attempt to elucidate briefly from a practical standpoint the significance of bank deposits and bank loans in the monetary system and to analyse the actual character of the processes which they involve. The task is being undertaken because it was felt by the Council of the Society that a paper on this subject and the discussion which it should provoke might help to clarify some of the confusion which has been evident in much of the popular discussion which has been taking place in this country on these topics for some time past. The facts of Irish banking will be regarded throughout as providing the real background upon which our conclusions are to be based.
Read on Friday, 18th December, 1942
Keywords: Commercial banking; Balance of transactions; 314.15